2010
DOI: 10.1007/s10681-010-0263-3
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of drought resistance and biomass by increasing the amount of glycine betaine in wheat seedlings

Abstract: Drought is a major agricultural menace reducing crop productivity and limiting the successful realization of land potential throughout the world. Therefore, breeding common wheat with improved drought-tolerance via genetic manipulation is of great importance. We have introduced the betA gene encoding choline dehydrogenase from Escherichia coli into common wheat (Triticum aestivum L.) by Agrobacterium-mediated transformation. Various levels of expression of the betA gene were confirmed by RT-PCR among the trans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
27
1
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(30 citation statements)
references
References 43 publications
(46 reference statements)
1
27
1
1
Order By: Relevance
“…These results demonstrate that GB pretreatment can im-prove the activity of antioxidant enzymes, help prevent reactive oxygen species and oxidative damage, alleviate membrane lipid peroxidation, and thus maintain the integrity and function of cell membranes (DaCosta and Huang, 2007;Hussain Wani et al, 2013). It has been reported that these mitigations of GB pretreatment attributed to the wheat seedlings in the oxidation reaction under drought stress (He et al, 2011).…”
Section: Discussionmentioning
confidence: 65%
“…These results demonstrate that GB pretreatment can im-prove the activity of antioxidant enzymes, help prevent reactive oxygen species and oxidative damage, alleviate membrane lipid peroxidation, and thus maintain the integrity and function of cell membranes (DaCosta and Huang, 2007;Hussain Wani et al, 2013). It has been reported that these mitigations of GB pretreatment attributed to the wheat seedlings in the oxidation reaction under drought stress (He et al, 2011).…”
Section: Discussionmentioning
confidence: 65%
“…These were made drought resistant via over accumulation of GB, protection of photosynthetic machinery from damage caused by dehydration and accumulation of trehalose respectively (62,63,64).…”
Section: Post Transcriptional Regulation Of Abamentioning
confidence: 99%
“…Developing high-yielding wheat cultivars under drought conditions in arid and semiarid regions is an important objective of breeding programs [5]. Although great efforts have been made in wheat drought resistance breeding, the decrease in agricultural productivity induced by drought stress still remains unsolved [8]. One reason is that the numerous germplasm resources were not effectively utilized in wheat breeding programs.…”
Section: Introductionmentioning
confidence: 99%